2011
DOI: 10.1016/j.intimp.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells ameliorate the histopathological changes in a murine model of chronic asthma

Abstract: Asthma therapies are effective in reducing inflammation but airway remodeling is poorly responsive to these agents. New therapeutic options that have fewer side effects and reverse chronic changes in the lungs are essential. Mesenchymal stem cells (MSCs) are promising for the development of novel therapies in regenerative medicine. This study aimed to examine the efficacy of MSCs on lung histopathology in a murine model of chronic asthma. BALB/c mice were divided into four groups: Group 1 (control group, n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 35 publications
(38 reference statements)
4
58
0
Order By: Relevance
“…We and others have found that in mouse models of mild Th2-eosinophilic mediated AAI, systemic administration of MSCs either during initial sensitization or during challenge significantly ameliorates both AHR and lung inflammation [27][28][29][30][31][32][33][34][35][36][37][38]. In the current study, we demonstrated that systemic MSC administration during challenge ameliorates AHR and lung inflammation in a more severe model of acute mixed Th2/Th17-mediated neutrophilic AAI induced by mucosal exposure to and challenge with adjuvant-free AHE.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We and others have found that in mouse models of mild Th2-eosinophilic mediated AAI, systemic administration of MSCs either during initial sensitization or during challenge significantly ameliorates both AHR and lung inflammation [27][28][29][30][31][32][33][34][35][36][37][38]. In the current study, we demonstrated that systemic MSC administration during challenge ameliorates AHR and lung inflammation in a more severe model of acute mixed Th2/Th17-mediated neutrophilic AAI induced by mucosal exposure to and challenge with adjuvant-free AHE.…”
Section: Discussionsupporting
confidence: 64%
“…Limited available data suggest that MSCs or MSCconditioned media can have effects in models of chronic AAI, but the mechanisms are unclear [27][28][29][30][31][32]. In the current studies, MSC administration during a recurrent challenge decreased AHR but not lung inflammation and paradoxically stimulated a significant increase in BAL fluid neutrophils.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Several studies have demonstrated the potential therapeutic effect of MSCs in different diseases: myocardial infarction [41,42,43,44], pulmonary fibrosis [45,46], pulmonary hypertension [47,48,49,50], emphysema [51,52,53], diabetes [54], sepsis [55,56], asthma [57], hepatic failure [58], acute renal failure [59] and ARDS [5,38,60,61,62,63,64]. In all preclinical studies, infused MSCs expanded in vitro were used.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Sun and colleagues (2011) demonstrated that the intravenous administration of autologous adipose-derived MSCs could attenuate the inflammatory response and oxidative stress in an acute rat ischemia-reperfusion lung injury model [12]. In experiments using asthma as a model for chronic lung disease, it was shown that the decline in lung function was inhibited by rat bone marrow MSCs [13,14]. This was achieved by reducing airway hyperactivity, inflammation, and remodeling.…”
Section: Adult (Progenitor) Stem Cellsmentioning
confidence: 99%